Photo-thermal driven ion separation device, preparation method and application
The photothermal-driven ion separation device addresses inefficiencies in lithium extraction from high Mg/Li ratio salt lakes by using solar energy and capillary forces for direct lithium chloride extraction, achieving high purity and reduced energy consumption.
Patent Information
- Application Number
- CN202411316380.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing methods for lithium extraction from salt lakes with high Mg/Li ratios are inefficient, costly, and environmentally harmful due to high osmotic pressure differentials and energy-intensive processes, and current membrane separation technologies are limited by mechanical strength and cost.
A photothermal-driven ion separation device using a porous substrate with a photothermal layer and ion separation membrane, utilizing capillary forces and solar energy for direct extraction of lithium chloride from salt lake brine, integrating a porous substrate, photothermal layer, and ion separation membrane to facilitate ion separation and evaporation.
The device achieves efficient, environmentally friendly lithium extraction with high purity and reduced energy consumption by using sustainable energy, capable of directly concentrating high-concentration brines and achieving a separation factor of over 30 and lithium chloride crystallization rates of 400 mg/m².
Smart Images

Figure CN119219123A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a membrane technology, and in particular to a photothermal driven ion separation device, a preparation method and an application thereof. Background Art
[0002] Lithium (Li) is a strategic, non-renewable resource used in high-tech products such as batteries, ceramics, glass, and alloys. With the surge in the use of consumer electronics and electric vehicles, lithium supply shortages are expected to become even more severe. Salt lake brines account for approximately 70% of the Earth's recoverable lithium, most of which is composed of high concentrations of magnesium ions. Currently, approximately 59% of lithium is produced from salt lake brines with low magnesium / lithium (Mg / Li) ratios. With 80% of my country's available lithium stored in salt lakes, lithium extraction from salt lakes is a crucial means of ensuring lithium supply. However, compared to the low Mg / Li ratios found in salt lakes in countries like Peru in South America, the Mg / Li ratios in my country's salt lakes are as high as tens or even hundreds, making lithium extraction from these lakes extremely challenging using traditional methods. Currently, only a very small number of these low Mg / Li ratio salt lakes are mined. Therefore, as the world's largest lithium consumer, my country is also a major lithium importer, relying on imports for approximately 80% of its lithium needs, presenting significant risks.
[0003] In order to alleviate the shortage of available lithium resources, people are increasingly interested in extracting lithium from brines with high Mg / Li ratios. There are also many methods for recovering lithium resources from salt lake water with high Mg / Li ratios. For example, Li can be extracted from brines with Mg / Li ratios of 325, 40 and 37.5 respectively by using tributyl phosphate / FeCl3 extraction, sodium metasilicate nonahydrate precipitation and lithium ion sieving method. The Mg / Li ratio of the original brine can be effectively reduced, but the loss of lithium resources and the generation of liquid waste remain unresolved. 2+ / Li + The mixture has good selectivity and recovery rate, but the current electrochemical device is expensive and the recovery stability is relatively poor. In addition, significant progress has been made in the separation of fine chemicals through membrane separation technology. Among them, nanofiltration membrane (NF) is becoming an efficient and environmentally friendly alternative for lithium extraction through the combination of size screening and charge repulsion effect. 2+ He Li + The hydration radius of the ions is very close, and the permeability of Li through polymer membranes is generally similar to that of Mg. 2+ / Li + At the same time, improved membrane separation methods have been developed for Mg 2+ / Li + Separation and selectivity of ion mixtures are achieved by nanofluidic devices made of two-dimensional materials and crystalline porous frameworks, which are limited by miniaturization size and high cost. 2+ / Li + Simple preparation methods for efficient extraction of lithium from brine remain an urgent need.
[0004] Therefore, membrane separation technology is widely used in high Mg 2+ / Li + The separation of mixed salt solutions shows greater potential. However, highly concentrated brine creates a high osmotic pressure differential across the membrane, requiring high applied pressures that far exceed the mechanical strength of the membrane assembly. Therefore, conventional NF membrane treatment processes typically involve diluting the highly concentrated brine 10-20 times with large amounts of fresh water during the pretreatment stage. Furthermore, NF membrane separation processes only produce a lithium-rich solution that requires further concentration to obtain a solid lithium product. This requires energy-intensive processes such as thermal distillation or high-pressure reverse osmosis to achieve the desired lithium-rich solution concentration. Summary of the Invention
[0005] To address the high cost and difficulty of ion separation in salt solutions, this invention provides a photothermal-driven ion separation device. This device utilizes the synergistic effect of an ion separation membrane and a solar evaporator to extract lithium chloride (LiCl) powder directly from salt lake brine. This method provides an efficient and environmentally friendly method for obtaining high-purity lithium directly from salt lake brine using only sustainable energy. This method reduces the integration of energy-intensive processes, thereby reducing energy consumption and operating costs.
[0006] In order to achieve the above-mentioned purpose, on the one hand, the technical solution adopted by the present invention is: a photothermal driven ion separation device, comprising a porous substrate, a pore structure is provided on the porous substrate, a photothermal layer is provided on the first surface of the porous substrate, and an ion separation membrane is provided on the second surface. The positional relationship between the first surface and the second surface is not limited, and preferably the first surface and the second surface are arranged relative to each other. When in use, the first surface is the upper surface and the second surface is the lower surface. The pore structure on the porous substrate connects the first surface and the second surface. This arrangement is conducive to the transport of water from the first surface to the second surface. The pore structure can be set in the following two ways: Method 1, the porous matrix itself can be a water-absorbing material or at least the inner wall material of the pore structure can be a hydrophilic material, and the pore structure has a microporous or nanoscale pore size. Water can be transported in the pore structure through capillary force; Method 2, the pore structure of the porous matrix is filled with hydrophilic material, and microporous or nanoscale water transfer channels are provided on the hydrophilic material. The capillary force generated by the water transfer channel serves as the power for water transfer. Under the action of capillary force, water passes through the ion separation membrane to the photothermal layer and evaporates. The ions that pass through the ion separation membrane are deposited in the water transfer channel.
[0007] As a preferred method, the porous matrix is a sand core with a pore size of G1-G6, preferably G6. The pore structure of the sand core is filled with hydrophilic material, and a nanoscale water channel is provided on the hydrophilic material. The water channel can generate a pressure of hundreds of MPa as water transmission power.
[0008] As a preferred approach, at least one of the ion separation membrane, photothermal layer, and hydrophilic material is synthesized in situ on the sand core to form an integrated structure. This arrangement helps improve device performance and stability. More preferably, all three are synthesized in situ on the sand core to improve layer adhesion and device stability.
[0009] As a preferred embodiment, the photothermal layer is a polymer layer that can absorb light and generate heat. The layer is a porous structure layer to facilitate the evaporation of water molecules in the film layer. Specifically, it can be polypyrrole, light-absorbing gel, or a high molecular polymer that can be blended with a black material. It can be formed into a porous film by phase inversion or electrospinning process, or formed in situ on the first surface of the sand core. The black material can be an organic polymer, such as polyaniline (PANI), or an inorganic substance, such as carbon nanotubes (CNTs), carbon black, carbon powder, graphene, MXene, etc. The photothermal layer can also be a gel dispersed with photothermal nanomaterials, such as a hydrogel or aerogel.
[0010] On the other hand, the present invention provides a method for preparing a photothermal-driven ion separation device. First, a porous substrate is selected, and a pore structure that penetrates the first surface and the second surface is provided on the porous substrate. A photothermal layer is provided on the first surface, and an ion separation membrane is provided on the second surface. Preferably, a hydrophilic material with a water transmission channel is provided in the pore structure.
[0011] Once again, the photothermal layer is preferably formed by alternating in-situ polymerization on the first surface of the sand core. On the one hand, the polymer has a strong light absorption capacity, which is beneficial to improving the evaporation efficiency of the device. On the other hand, it has good compatibility with the sand core and can form a stable bonding strength. The specific preparation method is as follows: S01 prepares an aqueous solution of pyrrole and an aqueous solution of ammonium persulfate, preferably with a mass ratio of pyrrole to ammonium persulfate of 1:(2-4); S02 applies the pyrrole aqueous solution to the first surface of the porous substrate; S03 applies the aqueous solution of ammonium persulfate to the first surface of the porous substrate obtained in S02 and allows it to react; S04 repeats steps S02 and S03 until the desired photothermal layer is formed. In the present invention, under the action of the oxidant (ammonium persulfate), an electrically neutral pyrrole monomer molecule loses an electron and is oxidized to a cationic free radical. Then, the two cationic free radicals combine to form a dication of dipolypyrrole, which undergoes disproportionation to form an electrically neutral dipolypyrrole. Then, the dipolypyrrole is oxidized, combined with cationic radicals, and then disproportionated to form a trimer. This reaction continues until a chain PPy molecule with a degree of polymerization of n is generated, and finally a photothermal layer is formed. The reaction formula is:
[0012]
[0013] As a more specific embodiment, the preparation method of the photothermal layer is as follows: (1) preparing a pyrrole aqueous solution: the preferred content range of pyrrole in the pyrrole aqueous solution is 0.5-5wt%, and preferably, 1.035mL of pyrrole solution is added dropwise to 50mL of aqueous solution, and the pyrrole aqueous solution is obtained after magnetic stirring for 10 minutes; (2) preparing an ammonium persulfate aqueous solution: the preferred content range of ammonium persulfate in the ammonium persulfate aqueous solution is 1-15wt%. A content lower than this will result in a prolonged self-polymerization time of the pyrrole monomer and incomplete coverage of the reactant polypyrrole on the surface of the sand core; a content higher than this will result in the reactant polypyrrole filling the internal pores of the sand core, reducing the porosity of the sand core, reducing the pore size of the sand core and reducing the hydrophilicity of the sand core. The preferred solution is prepared as follows: add 3.36g of ammonium persulfate white powder to 50mL of aqueous solution, stir magnetically for 10min and set aside; (3) apply pyrrole solution: use a dropper to draw a certain amount (determined according to the area of the selected sand core) of pyrrole aqueous solution and drop it onto the surface of the sand core, then use a brush to apply it evenly to ensure that the entire sand core surface is wetted; (4) apply ammonium persulfate solution: use a dropper to draw a certain amount (determined according to the area of the selected sand core) of ammonium persulfate aqueous solution and drop it onto the surface of the sand core, and use a brush to apply it evenly, and let it stand for 1 to 20min; (5) after wiping the residual aqueous solution on the surface of the sand core with dust-free paper, add a certain amount of pyrrole aqueous solution again to completely wet the membrane surface, and let it stand for a certain time, the reaction time is selected according to the reaction process, preferably 1 to 20min; (6) continue to repeat the above steps (4) and (5), for a total of three cycles, and terminate with the addition of ammonium persulfate solution. At this point, a photothermal layer for solar thermal conversion is prepared by in situ polymerization on the surface of the sand core.
[0014] As a preferred method, the hydrophilic material is synthesized in situ in the pore structure. This setting can regulate the pore size and wettability of the water transmission channel by regulating the polymer component, content or synthesis conditions. The hydrophilic material can be formed by the polymerization of two or more monomers, and can be selected from one or more materials such as polyethersulfone, polyvinylidene fluoride (PVDF), polyimide (PI), polyester (PP), polytetrafluoroethylene (PTFE), cellulose acetate (CA), polysulfone (PSF or PSU), polyacrylonitrile (PAN), hydrogel, etc., preferably polyethersulfone. The preparation method is: S01 dissolves polyethersulfone particles, polyethyleneimine, and polyethylene glycol in N,N-dimethylformamide to form a polymer solution; S02 pours the configured polymer solution into the pore structure of the porous matrix so that the pore structure is completely infiltrated by the polymer solution, and seals it for a set time; S03 takes out the porous matrix and performs non-solvent induced phase inversion in deionized water to form a hydrophilic polymer in the pore structure.
[0015] The hydrophilic material is once again preferably prepared by the following method: (1) adding polyethersulfone (PES) particles, polyethyleneimine (PEI) and polyethylene glycol (PEG) to N,N-dimethylformamide (DMF) solvent to prepare a polymer solution of a certain viscosity, wherein the polyethersulfone (PES) particles are 3-15 wt%, the polyethyleneimine is 0.5-10 wt%, and the polyethylene glycol is 0.5-3 wt%, the polymer solution is magnetically stirred at 25-50°C for 6-12 h, and then allowed to stand at room temperature for degassing for 8-12 h before use; (2) Slowly add the prepared polymer solution to the microporous sand core to completely soak it, and seal it for 24 hours; (3) Take out the microporous sand core that is completely soaked with the polymer solution inside, quickly place it in deionized water for water bath non-solvent induced phase transformation, and let it stand for 24 hours to complete the phase transformation of the polymer. After the phase transformation is completed, the pore structure of the sand core is filled with polymer; (4) Take out the sand core and transfer it to new deionized water to fully phase transform the internal polymer. After the phase transformation is completed, the porous matrix is stored in deionized water for use. After the polymer solution with N,N-dimethylformamide (DMF) as the continuous phase is made into a uniform liquid film, it is immediately immersed in water. DMF and polyethylene glycol (PEG) dissolve in water, so that the polyethersulfone (PES) polymer solution with the solvent as the continuous phase is transformed into a three-dimensional macromolecular network gel with polyethersulfone as the continuous phase, thereby forming a polyethersulfone separation membrane.
[0016] Further preferably, the polymer solution in step (1) is obtained by dissolving 7.5wt% polyethersulfone (PES) particles, 3.5wt% polyethyleneimine (PEI) and 2wt% polyethylene glycol (PEG) in DMF solvent, and the polymer solution is magnetically stirred at 40°C for 12h and allowed to stand for degassing for 10h. The type of polyethyleneimine (single chain or branched) and its molecular weight are not limited, preferably the polyethyleneimine molecular weight is 70,000 and the polyethylene glycol molecular weight is 400, which can provide more positively charged amino groups in the subsequently formed polymer membrane, thereby improving the adhesion of the in-situ polymerized nanofiltration layer, and also improving the hydrophilicity of the polymer membrane and the water flux of the polymer membrane. The type of non-solvent additive and its molecular weight are not limited, and the type of solvent used is not limited.
[0017] The ion separation membrane in the present invention is a nanofiltration membrane, which can be a commercially purchased finished membrane composited on a sand core, or a self-made membrane layer, preferably a self-made membrane layer. The charge properties and pore structure of the nanofiltration membrane can be optimized as needed to selectively transmit the desired ions and improve the ion separation efficiency. The preparation method of the ion separation membrane in the present invention is as follows: S01 prepares an aqueous solution of piperazine and sodium dodecylbenzenesulfonate as a first solution; prepares a n-hexane solution of trimesoyl chloride as a second solution; S02 immerses the second surface of the porous substrate in the first solution, takes it out after immersion for a set time, and immerses it in the second solution for polymerization reaction, generates a polymer on the second surface, and obtains a nanofiltration layer. As a preferred embodiment, the mass fraction of piperazine in the first solution is 0.1-5wt%, the mass fraction of sodium dodecylbenzenesulfonate is 0.1-3.6mmol / L, and the mass fraction of trimesoyl chloride in the second solution is 0.05-0.3wt%. Further preferably, the preparation method of the nanofiltration membrane is as follows: (1) preparing an aqueous solution containing 0.1-5 wt% piperazine (PIP) and 0.1-3.6 mmol / L sodium dodecylbenzenesulfonate (SDBS), and magnetically stirring at 20-40°C for 1-5 hours to obtain a completely dissolved PIP aqueous solution; (2) preparing an n-hexane (n-Hexane) solution containing 0.05-0.3 wt% trimesoyl chloride (TMC), and magnetically stirring at 20-40°C for 1-5 hours to obtain a completely dissolved TMC n-hexane solution; (3) immersing the second surface of the sand core in the PIP aqueous solution for 0.5-10 minutes; (4) removing the sand core from the PIP aqueous solution, removing excess water from the surface, and then immersing the sand core in a n-hexane solution containing TMC for 10-360 seconds to perform an interfacial polymerization reaction. The specific reaction formula is as follows:
[0018] The PIP monomer in the aqueous phase and the TMC monomer in the n-hexane solution undergo an irreversible rapid polycondensation reaction on the surface of the polymer-filled sand core, ultimately forming a dense nanofiltration layer in situ on the surface of the sand core; (5) the sand core is removed from the TMC n-hexane solution and slowly rinsed with pure n-hexane for 1-5 minutes to remove unreacted chemicals; (6) the microporous sand core with the polymer in situ is placed in an oven at 50-80°C and allowed to stand for 1-3 hours, preferably at 50°C for 2 hours, to obtain a nanofiltration layer formed integrally with the sand core; (7) the sand core is removed from the oven and immersed in deionized water at room temperature for use. In order to improve the retention rate of the nanofiltration layer and the extraction efficiency of lithium ions, in step (1), the mass fraction of PIP in the PIP & SDBS aqueous solution is 2wt%, the concentration of SDBS is 1.2mmol / L, and the concentration of TMC in the n-hexane solution is 0.15wt%, and all are stirred for 2 hours to obtain monomer solutions of the aqueous phase and the oil phase. The immersion time of the sand core in the aqueous solution and the oil solution was 1 min and 30 s, respectively.
[0019] In another aspect, the present invention provides a use for the aforementioned ion separation device. During operation, the device floats in the solution to be extracted, with the first surface facing upward, fully absorbing sunlight to generate heat. The second surface contacts the solution to be extracted, allowing the device to extract lithium ions or other ions. During operation, water drives permeable ions through the ion separation membrane and into the pore structure of the porous matrix. Upon heating, the water molecules convert into water vapor, escaping through the photothermal layer above, leaving the ions deposited within the pore structure. After the device has completed operation, the device is immersed in deionized water or the pore structure is rinsed with deionized water. The ions deposited within the pore structure dissolve in the deionized water, completing the ion extraction process.
[0020] The beneficial effects of the present invention include: 1. The photothermal driven ion separation device of the present invention uses the capillary force generated by sunlight and capillary channels as the power for water and ion transmission, without the need for external energy, and is energy-saving and environmentally friendly;
[0021] 2. By independently synthesizing hydrophilic materials on a photothermal-driven ion separation device, the present invention can freely control the hydrophilic properties and pore size of the hydrophilic material, and thus regulate the capillary force, making it suitable for various application scenarios;
[0022] 3. The present invention forms a photothermal layer on the porous body to achieve stable heat transmission on the device and improve the evaporation efficiency of water vapor;
[0023] 4. The present invention improves the stability of ion filtration performance by integrally forming a nanofiltration membrane on a porous substrate, and can regulate the charge and pore size of the nanofiltration membrane according to the properties of the separated ions, thereby improving the separation efficiency;
[0024] 5. Interfacial solar evaporation is a sustainable and cost-effective clean water production technology that uses heat generated by concentrated solar energy to promote water evaporation. The device in this invention is an effective method for obtaining high-purity lithium directly from salt lake brine using sustainable energy. It is environmentally friendly and reduces the integration of energy-intensive processes, thereby reducing energy consumption and operating costs.
[0025] 6. The device of the present invention can directly concentrate high-concentration, high-Mg-Li ratio salt lake brine, and the extraction efficiency can be adjusted by adjusting the pore size and surface charge properties of the bottom nanofiltration membrane. The device of the present invention is effective for Li + / Mg 2+ The separation factor can reach over 30, and the lithium chloride crystallization rate can reach 400 mg / m 2 Compared with existing salt lake ion resource extraction technology, the use of this device to treat high-concentration salt lake water can achieve lithium salt crystallization and recycling collection, ensuring that the resource extraction process is green, environmentally friendly, and economically efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The structural diagram of the hollow plywood encapsulated device in the present invention;
[0027] Figure 2 Pure water evaporation rate of the device in different salt solutions under three suns (3sun) illumination;
[0028] Figure 3 Separation factor of the device in different salt solutions;
[0029] Figure 4 Lithium chloride crystallization rate of the device in different salt solutions.
[0030] In the figure, 1 is the device, 2 is the hollow splint. DETAILED DESCRIPTION
[0031] The present invention will be further explained in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that the protection scope of the present invention is not limited to the specific embodiments.
[0032] The photothermal driven ion separation device in the present invention includes a porous matrix, which includes a first surface and a second surface arranged opposite to each other. A uniformly distributed pore structure is provided on the porous matrix as a channel, which penetrates the first surface and the second surface. A photothermal layer is provided on the first surface, which is a porous membrane layer. A nanofiltration membrane layer is provided on the second surface. The nanofiltration membrane layer can selectively pass certain ions, thereby realizing the separation of the ions from other ions. The pore structure is filled with a hydrophilic material, and a water transfer channel is provided on the hydrophilic material. The water transfer channel is a nanoscale channel, preferably a nanochannel of 10-220nm, which can generate a megapascal pressure of more than 18MPa. When in use, the first surface is upward as the upper surface, and the second surface is downward as the lower surface. The device floats in the solution to be extracted, the lower surface is in contact with the solution, and the upper surface is not in contact with the solution. The water in the solution and the ions to be extracted pass through the nanofiltration membrane to the hydrophilic material and are transmitted along the hydrophilic material. Under the action of the photothermal layer, the water absorbs heat and is converted into water vapor and escapes through the photothermal layer. The ions to be extracted are deposited in the hydrophilic material and eventually form solid crystals. The form of extraction of the solid crystals is not limited. The solid crystals can be dissolved by immersing the device, or by rinsing the device with deionized water to dissolve the solid crystals. The solid crystals can also be directly separated from the device in other forms.
[0033] In order to achieve the device can be stably floated on the solution, the porous matrix can be a buoyant material, through its own buoyancy, the device floats on the solution; the device can also be provided with a buoyancy member, through the buoyancy member to make the device float on the surface of the solution, the embodiment uses a hollow splint 2 with buoyancy arranged on both sides of the device 1, such as Figure 1 A gasket is provided between the hollow plywood 2 and the device 1 , and the hollow plywood 2 clamps the device 1 . The hollow plywood 1 is an annular body, clamping the device 1 around.
[0034] In this embodiment, the porous matrix is a sand core containing micropores, the thickness of the sand core is 3 mm, the pore diameter of the sand core is G6, and the pore diameter range is 1.2 to 10 μm.
[0035] The above devices can be used to separate ions with different charges or pore sizes, such as allowing Li + Monovalent ions such as SO4 pass through and block other multivalent ions, such as SO4 2- , Ca 2+ and Mg 2+ As one of its uses, it can separate lithium ions and magnesium ions to extract lithium ions. The device selectively intercepts magnesium ions and passes lithium ions, and lithium salts eventually crystallize and precipitate on the top of the photothermal layer.
[0036] The following is a further description of the device preparation method in the form of specific embodiments.
[0037] Example 1
[0038] The method for preparing the device comprises the following steps:
[0039] Step 1: In-situ synthesis of a photothermal layer on the first surface of the sand core. The synthesis method is:
[0040] (1) 1.035 mL of pyrrole solution (analytical grade) was added dropwise to 50 mL of aqueous solution and magnetically stirred for 10 min to obtain a 0.2 wt% pyrrole aqueous solution;
[0041] (2) Add 3.36 g of white ammonium persulfate powder to 50 mL of aqueous solution and stir magnetically for 10 min to obtain an ammonium persulfate solution;
[0042] (3) Use a dropper to draw a certain amount (determined according to the area of the selected sand core) of pyrrole aqueous solution and drop it onto the surface of the sand core. The amount of pyrrole aqueous solution per unit area of the sand core is 0.4 mL / m 2 , then use a brush to apply evenly to ensure that the entire sand core surface is wet;
[0043] (4) Use a dropper to draw a certain amount (determined according to the area of the selected sand core) of ammonium persulfate aqueous solution and drop it onto the surface of the sand core. The amount of ammonium persulfate aqueous solution added per unit area of the sand core is 0.4 mL / m 2 Use a brush to evenly apply it and let it stand for 3 minutes. During this process, pyrrole undergoes polymerization to form polypyrrole. The reaction formula is as follows:
[0044]
[0045] (5) After wiping the residual aqueous solution on the surface of the sand core with dust-free paper, 2Add the pyrrole aqueous solution to the sand core to completely wet the membrane surface, and let it react for 3 minutes;
[0046] (6) Repeat the above steps (4) and (5) for a total of three cycles, and terminate the reaction by adding the ammonium persulfate solution. At this point, a photothermal layer for solar thermal conversion is prepared by the in-situ polymerization reaction on the surface of the sand core.
[0047] Step 2: Fill the pore structure of the sand core with hydrophilic material. The preparation method is as follows:
[0048] (1) Polyethersulfone particles, polyethyleneimine, and polyethylene glycol were added to N,N-dimethylformamide (DMF) solvent to prepare a polymer solution of a certain viscosity. The concentration of polyethersulfone particles in the polymer solution was 7.5 wt%, the molecular weight of polyethyleneimine was 70,000, and the concentration was 3.5 wt%, and the molecular weight of polyethylene glycol was 400, and the concentration was 2 wt%. The polymer solution was magnetically stirred at 40°C for 12 h, and then allowed to stand at room temperature for 10 h for degassing before use.
[0049] (2) slowly adding the prepared polymer solution from the second surface to the microporous sand core pore structure to completely infiltrate it, and then sealing it for 24 hours;
[0050] (3) The microporous sand core containing the polymer solution was taken out and quickly placed in deionized water for water bath non-solvent induced phase inversion, and then allowed to stand for 24 h to complete the phase inversion of the polymer;
[0051] (4) Take out the polymer-filled microporous sand core and transfer it to new deionized water for storage. Step 3: In situ synthesize the nanofiltration membrane on the second surface of the sand core. The preparation method is:
[0052] (1) preparing an aqueous solution containing 2 wt% piperazine (PIP) and 0.15 mmol / L sodium dodecylbenzenesulfonate (SDBS), and magnetically stirring at 35°C for 2 h to obtain a completely dissolved PIP aqueous solution;
[0053] (2) preparing a n-hexane solution containing 0.15 wt% trimesoyl chloride (TMC) and stirring under magnetic stirring at 35°C for 2 h to obtain a completely dissolved TMC n-hexane solution;
[0054] (3) Immerse the second surface of the sand core in the PIP aqueous solution for 1 min, then remove it to remove excess surface moisture;
[0055] (4) Immerse the second surface in a hexane solution containing TMC for 30 seconds to perform interfacial polymerization. The polymerization reaction formula is:
[0056] ;
[0057] Where ※ represents piperazine or trimesoyl chloride monomer. During the reaction, the PIP monomer in the aqueous phase and the TMC monomer in the n-hexane solution undergo an irreversible and rapid polycondensation reaction on the second surface of the sand core, ultimately forming a dense nanofiltration layer in situ on the sand core surface.
[0058] (5) Remove the surface-polymerized sand core from the n-hexane solution containing TMC and rinse it slowly with pure n-hexane for 1 min to remove unreacted chemicals;
[0059] (6) Place the sand core in a 50°C oven for 2 hours to dry;
[0060] (7) Take out the sand core from the oven and soak it in deionized water at room temperature. Take it out when using it.
[0061] The resulting device was encapsulated using a hollow plywood and gasket. Both the plywood and gasket are annular and securely fastened around the top and bottom surfaces of the device. The plywood provides buoyancy, allowing the device to float on water. The device was then placed in a saline solution containing magnesium chloride and lithium chloride at a total concentration of 80 g / L, with a lithium ion to magnesium ion ratio of 1:1. The device's lithium extraction efficiency was tested under a three-sun light intensity for 48 hours.
[0062] Example 2
[0063] The difference from Example 1 is that the salt solution to be extracted is different. In this example, the device is placed in a mixed solution of lithium chloride and magnesium chloride, the mass ratio of lithium ions to magnesium ions in the solution is 1:1, and the total concentration of lithium chloride and magnesium chloride is 20 g / L.
[0064] Example 3
[0065] The difference from Example 1 is that the salt solution to be extracted is different. In this example, the device is placed in a mixed solution of lithium chloride and magnesium chloride, the mass ratio of lithium ions to magnesium ions in the solution is 1:1, and the total concentration of lithium chloride and magnesium chloride is 30 g / L.
[0066] Example 4
[0067] The difference from Example 1 is that the salt solution to be extracted is different. In this example, the device is placed in a mixed solution of lithium chloride and magnesium chloride, the mass ratio of lithium ions to magnesium ions in the solution is 1:1, and the total concentration of lithium chloride and magnesium chloride is 40 g / L.
[0068] The devices of Examples 1-4 were tested for water evaporation rate, separation factor, and lithium chloride crystallization rate. The separation factor was calculated as follows: separation factor = lithium-magnesium ion mass ratio after separation / lithium-magnesium ion mass ratio before separation. For example, assuming a lithium-to-magnesium ion mass ratio of 1:1 in the salt solution to be extracted, and a 20:1 mass ratio of lithium ions to magnesium ions entering the sand core pore structure, the separation ratio is (20:1) / (1:1) = 20.
[0069] The lithium chloride crystallization rate is calculated as follows: lithium is the mass of lithium chloride powder collected per unit area of the device by solar-powered operation per unit time. In the present invention, the lithium chloride powder collected by the device is dissolved in a certain volume of aqueous solution. The mass concentration of lithium ions in the aqueous solution is measured using an inductively coupled plasma spectrometer to infer the mass of the lithium chloride powder. For example, if the lithium ion concentration is 1 mg / L and the volume of the aqueous solution is 0.1 L, the mass of lithium is 0.1 mg, which is then divided by the operating area and operating time of the separation membrane to obtain the final lithium chloride crystallization rate.
[0070] The test results are as follows Figure 2-4 As shown by Figure 2 It can be seen that as the amount of the mixed brine solution of magnesium chloride and lithium chloride increases, the water evaporation rate and separation factor remain basically unchanged. Figure 4 It can be seen that with the increase of the mixed salt solution of magnesium chloride and lithium chloride, the crystallization rate of lithium chloride increases, indicating that the device can adapt to salt solutions of various concentrations, the separation efficiency is stable at more than 30, and in high-concentration salt solutions, it is beneficial to increase the crystallization rate of salt.
[0071] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A photothermal driven ion separation device, characterized in that: It comprises a porous matrix, a photothermal layer is arranged on the first surface of the porous matrix, the photothermal layer absorbs light and generates heat, an ion separation membrane is arranged on the second surface of the porous matrix, the ion separation membrane selectively transmits ions in the solution, the pore structure in the porous matrix connects the first surface and the second surface, and when in use, the ion separation membrane is in contact with the solution; The hole structure is arranged in the form of: the inner wall of the hole structure is a hydrophilic material, the hole structure is used as a water channel or the hole structure is filled with a hydrophilic material, and a water channel is arranged on the hydrophilic material; The capillary force generated by the water transport channel drives the water and permeable ions in the solution through the ion separation membrane to the pore structure of the porous matrix, the water evaporates in the photothermal layer, and the ions are deposited in the pore structure of the porous matrix.
2. The photothermal driven ion separation device according to claim 1, characterized in that: The ion separation membrane satisfies one of the following: —the photothermal layer is a polymer, and the polymer of the photothermal layer is formed by in-situ polymerization on the first surface of the porous substrate; —The pore structure of the porous matrix is filled with a hydrophilic material, and the hydrophilic material is generated in situ in the pore structure; - The ion separation membrane is formed by in-situ polymerization on the second surface of the porous matrix.
3. The photothermal driven ion separation device according to claim 1, characterized in that: The ion separation membrane satisfies one or more of the following combinations: —The photothermal layer is polypyrrole, - the ion separation membrane is a nanofiltration membrane, - The water transfer channel is a nanoscale channel.
4. A method for preparing a photothermal driven ion separation device, characterized in that: The method comprises the following steps: selecting a porous substrate, the porous substrate comprising a first surface and a second surface, the first surface and the second surface being connected through a pore structure, and a water transfer channel being arranged in the pore structure; Disposing a photothermal layer on the first surface of the porous substrate; Disposing an ion separation membrane on the second surface of the porous substrate; The photothermal layer is formed by in-situ polymerization on the first surface of the porous matrix or / and the ion separation membrane is formed by in-situ polymerization on the second surface of the porous matrix or / and a hydrophilic material containing a water transport channel is arranged in the pore structure of the porous matrix, and the hydrophilic material is in-situ polymerized in the pore structure of the porous matrix.
5. The method for preparing a photothermal driven ion separation device according to claim 4, characterized in that: The photothermal layer is formed by in-situ polymerization on the first surface of the porous substrate. The preparation method of the photothermal layer comprises the following steps: S01 preparing an aqueous solution of pyrrole and an aqueous solution of ammonium persulfate; S02 coating the pyrrole aqueous solution on the first surface of the porous substrate; S03: coating an aqueous solution of ammonium persulfate on the first surface of the porous substrate obtained in S02, and allowing to react; S04: repeating steps S02 and S03 until the desired photothermal layer is formed.
6. The method for preparing a photothermal driven ion separation device according to claim 5, characterized in that: The concentration of each solution in step S01 satisfies one or a combination of the following: - The mass fraction of pyrrole in the aqueous solution is 0.5-5wt%; —The mass fraction of ammonium persulfate in the ammonium persulfate aqueous solution is 1-15wt%.
7. The method for preparing a photothermal driven ion separation device according to claim 4, characterized in that: The hydrophilic material filled in the pore structure of the porous matrix is a hydrophilic polymer, and the preparation method of the hydrophilic polymer comprises the following steps: S01 dissolving polyethersulfone particles, polyethyleneimine, and polyethylene glycol in N,N-dimethylformamide to form a polymer solution; S02: pouring the prepared polymer solution into the pore structure of the porous matrix, so that the pore structure is completely infiltrated by the polymer solution, and sealing it for a set time; S03: taking out the porous matrix and placing it in deionized water for non-solvent induced phase transformation to form a hydrophilic polymer in the pore structure.
8. The method for preparing a photothermal driven ion separation device according to claim 7, characterized in that: The mass fraction of polyethersulfone in the polymer solution is 3-15wt%, the mass fraction of polyethyleneimine is 0.5-10wt%, and the mass fraction of polyethylene glycol is 0.5-3wt%.
9. The method for preparing a photothermal driven ion separation device according to claim 4, characterized in that: The ion separation membrane is a nanofiltration layer, and the preparation method comprises the following steps: S01: preparing an aqueous solution of piperazine and sodium dodecylbenzene sulfonate as a first solution; preparing a n-hexane solution of trimesoyl chloride as a second solution; S02: immersing the second surface of the porous substrate in the first solution, taking it out after immersion for a set time and immersing it in the second solution for polymerization reaction, generating a polymer on the second surface to obtain a nanofiltration layer.
10. The method for preparing a photothermal driven ion separation device according to claim 9, characterized in that: The mass fraction of piperazine in the first solution is 0.1-5wt%, the mass fraction of sodium dodecylbenzenesulfonate is 0.1-3.6mmol / L, and the mass fraction of trimesoyl chloride in the second solution is 0.05-0.3wt%.
11. Use of a photothermal driven ion separation device, characterized in that: The photothermally driven ion separation device described in any one of claims 1 to 3 or the photothermally driven ion separation device prepared by the preparation method described in any one of claims 4 to 10 is used to extract ions from a solution, the photothermally driven ion separation device floats on the solution, and the ion separation membrane is in contact with the solution.
Citation Information
Patent Citations
Method for preparing polymeric blend membrane by nonsolvent induced gel phase separation method
CN108525531A
Polysulfone-based photothermal conversion composite membrane for solar water evaporation and preparation method thereof
CN112128996A
Photo-thermal evaporation membrane based on waste MBR membrane component and preparation method and application of photo-thermal evaporation membrane
CN113975977A
Ion separation device, method and application
CN115353247A
Nanofiltration membrane for extracting lithium from salt lake and preparation method of nanofiltration membrane
CN117563440A
